Penerapan Electronic Endorsement atas Pemasukan Barang Kena Pajak Berwujud dari Tempat Lain Dalam Daerah Pabean (TLDDP) ke Kawasan Bebas Batam sebagai Purwarupa Pembangunan Ekosistem Kepatuhan Pajak dan Kemudahan Berusaha - Ryan Nugraha; Rd Kusyeni (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Electronic endorsement is one of the pivotal policies to provide automation service for the taxpayers and oversee tax compliance in the Free Trade Zone. Therefore, the policy implementation is necessary to be evaluated. Currently, we revealed that the revenue administration faced an absence of an information system to intercept the parties who are not entitled to receive the VAT facility. Furthermore, the remote taxpayers must physically come to the Tax Office when applying for Tax Endorsement. As a result, the compliance cost is increasing. Lastly, the volume of Endorsement documents in the Batam Tax Office is very high, thereby increasing the administration cost for the DGT. To further understand the implementation of electronic endorsement, we interviewed ten stakeholders from the DGT. The writers compiled a matrix to measure policy effectiveness based on four dimensions of Steers Theory, namely management, environment, human resources, and organization. The writers also added another four dimensions in the form of outputs level, satisfaction, product innovation, and intensity achieved based on the theory from Krech et.al. The research showed eight points. First, most informants said improving standard operating procedures, regulations, and IT infrastructures is needed in terms of the management aspect. Second, interoperability cooperation and a new business process are essential. Third, the research showed that the officer conducted professional service for the taxpayers. Fourth, the current Madya Batam Tax Office was still suitable for providing endorsement services in terms of organization. Fifth, most informants support that an easy bureaucracy will improve the services. Sixth, all informants are satisfied with the services. Seventh, the speed of service time is the most important thing at the services level. Lastly, the electronic endorsement policy has been increasing the tax compliance ecosystem. The result suggests that, in general, the Electronic Endorsement policy has been quite effectively implemented, especially in improving tax compliance and ease of doing business in the Batam Free Trade Zone.